Challenges for Adolescents With Congenital Heart Defects/Chronic Rheumatic Heart Disease and What They Need: Perspectives From Patients, Parents and Health Care Providers at the Institut Jantung Negara (National Heart Institute), Malaysia - Tye, Sue Kiat; Kandavello, Geetha; Wan Ahmadul Badwi, Syarifah Azizah; Abdul Majid, Hariyati Sharima (Frontiers in Psychology, 2021)
Objectives: To describe the experiences and challenges faced by adolescents with moderate 3 and severe congenital heart defects (CHD) / Chronic Rheumatic Heart Disease (CRHD) and to 4 determine the needs for the development of Adolescent Transition Psychoeducational Program. 5 Methods: Seven adolescents with moderate to severe CHD/ CRHD, six parents and four health 6 care providers in Institute Jantung Negara (National Heart Institute) were invited for a semi-structure 7 interview. The qualitative data was analyzed by using Atlas.ti 7 program using triangulation 8 methods. 9 Results/conclusions: Five themes of adolescents’ experience and challenges related to 10 (1) emotional / psychological issues, (2) progress of illness, (3) relationship issues, (4) 11 future preparation, and (5) school and community, were identified together with their eleven 12 categories. The staffs expressed their support towards the development of Adolescent Transition 13 Psychoeducational Program and these adolescents with CHD/ CRHD and their parents claimed 14 that they were willing to participate in the program if their schedule allowed. Their suggestion for the elements to be included into the program were classified into two themes, which are (1) self- 16 management on illness and life and future and (2) social supports together with four categories. In 17 conclusion, the findings from the current situation analysis acts as a basis for conceptual framework 18 in developing the Adolescent Transition Psychoeducational Program, in order to empower the 19 adolescents with CHD/ CRHD to manage their challenges during the transition phase towards 20 adulthood.